Flower quality parameter as affected by moisture content during value addition through flower drying - Deepti Singh; Kavita Kumari; Priyanka Kumari; Rakesh Kumar (Annals of Agricultural Research, 2026)
Moisture content studies were carried out among sixteen flowers including selection of quality floral raw material for dehydrated value addition and product preparation. The results revealed that optimum floral moisture content directly influenced the quality, natural colour retention and shelf life of dry flowers. Moisture content varied 6.81% (helichrysum) to 15.23% (dahlia) based on flower texture, size and utility. In dry flowers, high moisture content (12 to 15%) than optimum levels lead to more shrinkage and microbial infestation with lesser shelf life, whereas very low levels of moisture (less than 5%) causes flower brittleness and shattering. Hence an optimum moisture content on dry weight basis (7-9 percent) was found optimum for quality dry flowers selection with higher shelf life of more than four years.